An application of the principle of the competitive space demands accelerator to the assessment of the mobile communication market development in the Czech Republic - Robert Zich; Karolína Svobodová; Jitka Veselá (Trends Economics and Management, 2018)
Purpose of the article: The article presents the conclusions of an empirical study focused on the dynamics of changes of the Czech mobile communication market at the moment of significant change of the pricing policy in 2013. The evaluation of the dynamics of changes is based on the competitive space demands accelerator mechanism, which is a theoretically developed concept explaining specific links between the growing customer demands and company competitiveness development. The study presented in this article has verified the validity of this concept. Methodology/methods: The presented results are significantly supported by ten years of the intensive research activity mapping aspects of competitive behavior of mobile service providers in the Czech Republic. The research methodology is based on a qualitative research case study. Scientific aim: The main scientific aim is an empirical verification of the theoretically developed concept explaining the paradox of accelerated growth of customers' demand caused by the company endeavor to increase its competitiveness in the mobile communication industry. Findings: The development of the mobile communication market in the Czech Republic at the moment of principle change in the structure and form of offered subscriptions in associations with the pricing policy in the year 2013 proved the validity of the mechanism of the influence of the competitive space demands accelerator. Conclusions: The main conclusion can be summarized into three points. The first is the fact that a significant part of the increase in requirements and demands of the market is called by the activity of companies rather than the natural growth of customers' requirements. The second, extremely intensive depreciation of the potential advantage in the sense of competitive differentiation and perceived value can be explain by the mechanism of the accelerator. The third is confirmation of validity of criticism of the concept of sustainable advantage especially in the context of the created customer value.
Keywords: L1; L14; 650; competitive space; demand acceleration; competitiveness; competitive advantage; deprivation of advantage; convergence of competitive behavior